2003
DOI: 10.1038/sj.bmt.1703856
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment of high-risk stage II breast cancer with doxorubicin followed by high-dose chemotherapy and autologous stem-cell transplantation: a single-institution experience with 132 consecutive patients

Abstract: Several studies have shown conflicting results with the use of intensive consolidation chemotherapy for breast cancer. The aim of the present study was to investigate the efficacy, feasibility and toxicity of high-dose chemotherapy with stem cell support in patients with high-risk stage II breast cancer. From February 1994 to November 1998, 132 consecutive patients with multinode positive breast cancer were entered to the study. In total, 86 patients had >or=10 positive axillary lymph nodes, and 46 had 4-9 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…This was attributed to the selection of a noncarmustine-based transplant protocol, the use of peripheral blood stem-cell support, and better supportive care. This low treatment-related mortality was in accordance with other studies (8,10,11,13,18,21,24).…”
Section: Discussionsupporting
confidence: 79%
“…This was attributed to the selection of a noncarmustine-based transplant protocol, the use of peripheral blood stem-cell support, and better supportive care. This low treatment-related mortality was in accordance with other studies (8,10,11,13,18,21,24).…”
Section: Discussionsupporting
confidence: 79%
“…In some studies a TRM of 2–3% for patients with BC have been reported (11, 14). A TRM below 1% was reported with cyclophosphamide, thiotepa, carboplatin conditioning (15, 16), which was also the conditioning regimen used in the Scandinavian Breast Group study. No early treatment‐related deaths were observed in the cohort of 63 patients transplanted for CLL.…”
Section: Discussionmentioning
confidence: 99%